(untitled) (Journal of Asian Development Studies, 2023)
This study investigates the Exchange Rate (ER) response to fundamental economic factors such as money supply, output, interest, and inflation shocks. The dynamic responses of exchange rate, output, money supply, expected inflation, and nominal interest rate in response to macroeconomic disturbances and their relative effects are analyzed using the impulse response function. The study also attempts to explore the contribution of the macroeconomic policy shocks to the forecast error variance of real ER and other macroeconomic variables of the study. Both impulse responses and FEVD are computed by imposing identification restriction after the estimation of reduced form VAR model. For this purpose, the SVAR model is employed by using the panel data over the period 1991 to 2020 for 84 developing countries. The impulse response function and variance decomposition are estimated based on the structural decomposition. The study’s findings indicate that fundamental macroeconomic variables play a significant role in determining the behavior of exchange rates in the case of developing countries.